(untitled) (Research, Society and Development, 2022)
Objectives: List the possible causes that make it difficult for users to access primary health care in Brazil and analyze the instruments used by nurses to ensure access to primary health care for all users in Brazil. Methodology: This is an integrative literature review, which will address the role of nurses in terms of accessibility to health in Brazil. Results: To achieve the objectives of this phase, tables were built with characteristics of the analyzed articles and a categorization table of the studies. Discussion: It is observed that there are numerous factors that make it difficult for users to access and access health facilities. Final Considerations: It is possible to conclude that the nursing professional is a fundamental instrument in the health system, being characterized as the profession of the future, having the understanding of the individual, not only as a sick being, but a being in a singular and complex way, In addition, the articles that were part of the literature review showed that the knowledge of the professional nurse about ensuring access to health is still scarce in most cases, which calls into question the development of qualification strategies for this professional regarding the guarantee of access to health.